Sphingosine 1‐phosphate attenuates neuronal dysfunction induced by amyloid‐β oligomers through endocytic internalization of NMDA receptors. (12th August 2022) - Bigi, Alessandra; Cascella, Roberta; Fani, Giulia; Bernacchioni, Caterina; Cencetti, Francesca; Bruni, Paola; Chiti, Fabrizio; Donati, Chiara; Cecchi, Cristina
Abstract : Soluble oligomers arising from the aggregation of the amyloid beta peptide (Aβ) have been identified as the main pathogenic agents in Alzheimer's disease (AD). Prefibrillar oligomers of the 42‐residue form of Aβ (Aβ42 O) show membrane‐binding capacity and trigger the disruption of Ca 2+ homeostasis, a causative event in neuron degeneration. Since bioactive lipids have been recently proposed as potent protective agents against Aβ toxicity, we investigated the involvement of sphingosine 1‐phosphate (S1P) signalling pathway in Ca 2+ homeostasis in living neurons exposed to Aβ42 O. We show that both exogenous and endogenous S1P rescued neuronal Ca 2+ dyshomeostasis induced by toxic Aβ42 O in primary rat cortical neurons and human neuroblastoma SH‐SY5Y cells. Further analysis revealed a strong neuroprotective effect of S1P1 and S1P4 receptors, and to a lower extent of S1P3 and S1P5 receptors, which activate the Gi ‐dependent signalling pathways, thus resulting in the endocytic internalization of the extrasynaptic GluN2B‐containing N ‐methyl‐ D ‐aspartate receptors (NMDARs). Notably, the S1P beneficial effect can be sustained over time by sphingosine kinase‐1 overexpression, thus counteracting the down‐regulation of the S1P signalling induced by Aβ42 O. Our findings disclose underlying mechanisms of S1P neuronal protection against harmful Aβ42 O, suggesting that S1P and its signalling axis can be considered promising targets for therapeutic approaches for AD. Abstract : Both exogenous and endogenous sphingosine 1‐phosphate (S1P) rescue neuronal Ca 2+ dyshomeostasis induced by prefibrillar oligomers of Aβ42 peptide (Aβ42 O) in neuronal cells. S1P activates its specific receptors (S1PRs), which stimulate the endocytic internalization of the extrasynaptic GluN2B‐containing N ‐methyl‐ D ‐aspartate receptors (NMDARs). Notably, the S1P beneficial effect can be sustained over time by sphingosine kinase‐1 (SK1) overexpression, thus counteracting the down‐regulation of the S1P signalling induced by Aβ42 O. Created with BioRender.com .